IDIOPATHIC GRANULOMATOUS MASTITIS: DIAGNOSIS AND FOLLOW-UP WITH MAGNETIC RESONANCE IMAGING - Andrade, Felipe Eduardo Martins de; Pincerato, Kátia Maciel; Docema, Marcos Fernando; Barros, Alfredo Carlos Simões Dornellas de (Mastology, 2017)
Granulomatous mastitis is a rare and benign condition of the breast that, in some cases, has an unknown etiology of benign inflammatory disease know as idiopathic mastitis. Your diagnosis is usually made by exclusion. Imaging tests have shown nonspecific findings that may suggest an inflammatory disease, a carcinoma, or no changes. A differential diagnosis should be made with other causes of mastitis, always alerting to the risk of inflammatory carcinoma. Imaging tests are more useful to rule out malignancy than to confirm idiopathic granulomatous mastitis. Because both imaging and physical examination can mimic a malignant lesion of the breast, the histopathological report is fundamental to establish the diagnosis. Its etiology remains unknown, so the treatment is controversial in the literature, with some authors recommending surgery, others immunosuppression, and, finally, some antibiotics. We report the case of a 21-year-old woman with a suspected lesion in the breast associated with papillary discharge. During the investigation, there was a 12 x 6 x 8.5 cm enhancement on magnetic resonance imaging associated with inflammatory signs on the skin and lymph nodes. Anatomopathological examination revealed a idiopathic granulomatous mastitis. The enhancement disappeared completely after conservative treatment with corticosteroids. Mammography and ultrasound may also demonstrate nonspecific changes, such as focal asymmetry, undefined mass, or distortion. Despite the limitations of the imaging studies, it has been demonstrated in this report that MRI can be used to monitor the clinical response to conservative treatment and follow-up by the risk of recurrence.